Power wheelchair adaptive team sport involvement: Experience, impact on quality of life, and physical fitness - Hayward, L.; Hogan, D.; Melam, A.; Raine, L.; McCullough, A.; Bell, A. (Research Quarterly for Exercise and Sport, 2025)
Purpose: Adults with disabilities can benefit from physical activity. Athletic activity for adults with disabilities requires adaptation to their physical and/or intellectual limitations. However, few adaptive, inclusive sports programs exist for power wheelchair users. Methods: A multi-method, qualitative case-study design was used to describe the experiences of athlete participation in powerful wheelchair adaptive team sports, specifically, soccer and volt hockey. Ten qualitative interviews with 5 players from the US and 5 from Scandinavia explored player experiences with adaptive team sports. The authors assessed overall health once using the World Health Organization Quality of Life Survey (WHOQOL-BREF). Subsequent heart rate data were collected from players while at rest and during adaptive team sport scrimmages. Results: Four qualitative themes described adults with disability experiences: Community; Personal gain; Competition; and Barriers. WHOQOL-BREF means averaged 60 points for all four domains, no significant differences existed between US and Scandinavian players. Heart rate data demonstrated a significant increase in heart rate during scrimmage compared to rest. Conclusion: Adaptive team sports provided participants with valuable social interaction, decreased isolation, and increased opportunities for mentorship and advocacy. Participants reported personal gain related to mental, emotional, and physical benefits not found elsewhere. Competition allowed participants to set both team and individual goals for improvement. Barriers to play concerned equipment, volunteers, and ableist attitudes.